IMPACT OF OBESITY ON PULMONARY FUNCTIONS AMONG YOUNG NON-SMOKER HEALTHY FEMALE OF SHAH ALAM, MALAYSIA - Bhattacharjee, Aniruddha; Thygoo, Ariitharan A/l; Rammohan, Subramanian (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The sedentary lifestyle, physical inactivity, and unhealthy diet of Malaysian female have become important contributing factors to the rise of obesity. Studies on pulmonary function in relation to obesity are very few in Malaysia. Therefore, the study was aimed to evaluate the effect of obesity on pulmonary functions among young adult healthy female students of Shah Alam, Malaysia. Methods: A cross-sectional comparative study was conducted in a total of 100 (50 obese and 50 non-obese) adult non-smoker healthy female students aged 18–25 years. Forced vital capacity (FVC), forced expiratory volume in 1 sec (FEV1), FEV1 as a percentage of FVC (FEV1/FVC%), maximum midexpiratory flow rate (FEF 25–75%), and peak expiratory flow rate (PEFR) were measured using a computerized spirometer. Body weight, height, waist circumference (WC), and hip circumference (HC) were measured. Results: The mean FVC (L), FEV1 (L), FEV1/FVC ratio, FEF 25–75% (L/s), and PEFR (L/s) of obese group were marginally lower than non-obese control group, but the differences were not statistically significant. WC and waist–hip ratio exhibited significant (p<0.05) inverse correlation with all pulmonary function measurements except FEV1/FVC%. However, body mass index had no significant correlation with any spirometric variables in studied obese females. Conclusion: There was no significant effect of obesity on pulmonary functions in the studied Malaysian females. However, abdominal obesity had more impact on the impairment of pulmonary functions than overall relative obesity.